KONFLIK SOSIAL ANTARA OJEK PANGKALAN DAN GOJEK DI KOTA SURAKARTA - Dwi Nurindah Rahayu; Ahmad Zuber (Journal of Development and Social Change, 2019)
In this research try to raise the theme of conflict research between traditional ojek drivers and GoJek in the city of Surakarta. GoJek is present with various services needed and influential for the community in all activities quickly and efficiently. But on the other hand Gojek is a rival for traditional ojek drivers and the exsistence of GoJek triggers conflict. The purpose of this research is to find out how conflicts occur between traditional ojek drivers and GoJek, what are the forms of conflict, factors that affect conflict and how conflict prevention efforts. The theory used is social conflict theory from Lewis L. Coser. Types of research used in this phenomenon is descriptive qualitative, with data collection techniques through observation, interviews and from secondary data and documentation. The sample uses a purposive sampling technique. With the stipulation of the informants of the traditional ojek drivers,GoJek drivers and traditional ojek and GoJek consumers. The data validity technique uses source triangulation. While the data analysis uses 3 channels namely data reduction, data presentation and drawing conclusions.The results showed that the conflict that occurred between traditional ojek driver and GoJek occurred due to the reduced income of ojek, because people preferred to use GoJek. The form of conflict that occurs between conventional ojek and GoJek is divided into two, namely the form of manifest conflict (open) and latent conflict (closed). Forms of manifest conflicts include beatings, quarrels and struggles for attributes. While latent forms of conflict include jealousy and envy and disappointment. Conflict between conventional ojek and GoJek is caused by several factors including land limitations, system differences, and tariff differences. So that the conflict does not continue, several efforts have been made to overcome the conflict, namely the determination of the red zone boundary, warning or warning, and reporting to the authorities.